A Minimally Invasive Approach Toward Thoracic Epidural Abscess in a Young Child - Himanshu Gurunath Kulkarni; Sushil Tippanawar; Ranjeet Rajure; Gurunath S. Kulkarni (Indian Spine Journal)
Spinal epidural abscesses (SEAs) are a result of bacterial infections. They represent about 7% of vertebral infections and usually occur in subjects with predisposing co-morbidities such as diabetes mellitus, chronic renal failure, cancer, and immunodeficiency. Interestingly, the source of infection is not identifiable in 20%–40% of cases. The diagnosis of SEA is defined by the presence of a classical clinical triad of symptoms such as focal back pain, fever, and neurologic deficit. Standard laminectomies/hemi-laminectomies have been gold standard treatment approaches in decompression of the abscess, although long duration laminectomies or multilevel local laminectomies at an early age can lead to delayed instabilities and kyphotic deformities in the growing spine. We present a case of a 13-year-old girl having spontaneous thoracic epidural collection without any obvious trauma, medical co-morbidity, or preexisting infection. She was treated with a novel minimally invasive technique, being reported for the first time, through aspiration of the abscess spanning over nine vertebral levels with an epidural catheter, followed by administration of appropriate intravenous antibiotics based on the culture and sensitivity. The child recovered well neurologically.